2020
DOI: 10.5194/acp-2020-820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interhemispheric transport of metallic ions within ionospheric sporadic E layers by the lower thermospheric meridional circulation

Abstract: Abstract. Long-lived metallic ions in the Earth's atmosphere/ionosphere have been investigated for many decades. Although the seasonal variation in ionospheric sporadic E layers was first observed in the 1960s, the mechanism driving the variation remains a long-standing mystery. Here we report a study of ionospheric irregularities using scintillation data from COSMIC satellites and identify a large-scale horizontal transport of long-lived metallic ions, combined with the simulations of the Whole Atmosphere Com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, both ionosondes and VHF radars suffer from a scarcity of site distribution that cannot form a dense network for routinely monitoring of E s with a high spatial resolution. On the other hand, the technique of Global Navigation Satellite System (GNSS) radio occultation (RO) is employed in E s detection benefitting from its global coverage (e.g., Chu et al., 2014; Yeh et al., 2014; Yue et al., 2015; Yu et al., 2021). But the incontinuity of RO measurement makes it difficult to monitor E s over specific regions continuously, thus is more favorable for E s investigation on a climatologic sense (e.g., Chu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, both ionosondes and VHF radars suffer from a scarcity of site distribution that cannot form a dense network for routinely monitoring of E s with a high spatial resolution. On the other hand, the technique of Global Navigation Satellite System (GNSS) radio occultation (RO) is employed in E s detection benefitting from its global coverage (e.g., Chu et al., 2014; Yeh et al., 2014; Yue et al., 2015; Yu et al., 2021). But the incontinuity of RO measurement makes it difficult to monitor E s over specific regions continuously, thus is more favorable for E s investigation on a climatologic sense (e.g., Chu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yu et al. (2021a) simulated the global horizontal transport of metallic ions and found that seasonal dependence of the Es is consistent with the interhemispheric transport of long‐lived metallic ions by the winter‐to‐summer lower thermospheric meridional circulation. Thus, the seasonal dependence of the Es is the combined effect of different mechanisms and is still mysterious.…”
Section: Discussion and Summarymentioning
confidence: 73%
“…Recently, Yu et al. (2021) found that the 27‐day and 13.5‐day oscillations in the high‐latitude Es layers correlated well with the geomagnetic activity Dst and Ap indices. Thus, it is necessary to analyze the disturbances of the geomagnetic and solar activities.…”
Section: Discussion and Summarymentioning
confidence: 93%
See 2 more Smart Citations